Information Security Policy: Conditions, Threats and Implementation in the International Environment - Bajor, Piotr (2022)
Information security is one the key aspects of modern security and its importance has been significantly increasing in contemporary international relations. This publication presents the results of studies on several key aspects related to this issue. The publication contains results of research on considerations related to information security and its implementation, as well as research on social media, analysed through the lens of the object and subject of disinformation activities.
Keywords: disinformation; geopolitics; Ukraine; hybrid war; social media